2021
DOI: 10.1080/13814788.2021.1959911
|View full text |Cite
|
Sign up to set email alerts
|

Effects of access to radiology in out-of-hours primary care on patient satisfaction and length of stay

Abstract: KEY MESSAGESDirect access to radiology by the GP cooperative reduces the total LOS of trauma patients who require conventional radiology imaging. Patients slightly more appreciate GP cooperatives with unlimited access to radiology than those without or with limited access (in restricted time frames).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 20 publications
(35 reference statements)
2
13
0
Order By: Relevance
“…An additional advantage of co‐location is the possibility of direct access to hospital diagnostics, such as radiology facilities. Previous Dutch studies assessed the effect of GPs' out‐of‐hours access to radiology facilities and found a substantial decrease in ED trauma patient referrals and increased patient satisfaction levels 5,6,16 . Consistent with those studies, the use of diagnostics by GPs in our study seemed adequate.…”
Section: Discussionsupporting
confidence: 89%
“…An additional advantage of co‐location is the possibility of direct access to hospital diagnostics, such as radiology facilities. Previous Dutch studies assessed the effect of GPs' out‐of‐hours access to radiology facilities and found a substantial decrease in ED trauma patient referrals and increased patient satisfaction levels 5,6,16 . Consistent with those studies, the use of diagnostics by GPs in our study seemed adequate.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies that specifically deal with treatment of fractures, both in hospitals and the primary health care service, find similar figures of patient satisfaction with diagnosing and treatment of fractures. [ 25 , 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, also elsewhere in Norway and Europe x-ray examinations and fracture treatment are carried out and X-rays are sent to the nearest hospital for assessment and can be discussed with a radiologist and orthopedist. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…The 23 studies included in this review used various study types. There were six cohort studies [21][22][23][24][25][26], four randomised controlled trials [27][28][29][30], four observational studies [13,[31][32][33], three cross-sectional studies [34][35][36], three questionnaire studies [6,37,38], one retrospective analysis [39], one feasibility study [40], and one systematic review [3].…”
Section: Methodsmentioning
confidence: 99%
“…Seven studies were based in Denmark [21, 24-25, 28-30, 40], seven in the UK [3,13,23,27,36,38,39], six in the Netherlands [22,26,[31][32][33]35], two in Ireland [6,37], and one in Italy [34].…”
Section: Methodsmentioning
confidence: 99%